KARAKTERISTIK EDIBLE FILM SODIUM CASEINATE LIANG-TEH KAYA ANTIOKSIDAN - Dewi, Yohana Sutiknyawati Kusuma; Fitri, Utami Destia Fitri; Saputri, Nur Endah (BPFP Faperta UNIB, 2024)
In general, food packaging materials are divided into two major groups: bio and non-biodegradable. Currently being developed is biodegradable packaging, including edible films. The application of edible films as packaging with carriers of antioxidants and colorants. One alternative of natural antioxidant to applied in edible films is liang-tea. The liang-tea contains of alkaloids, flavonoids, phenols, and tannins, that contribute antioxidant activity. This research aims to determine the concentration of infusion liang-tea that produces the best characteristics of sodium caseinate edible film that rich antioxidant. The research used a randomized block design with a single treatment of the concentration of infused liang-tea of 0, 25, 50, 75, 100, 125, and 150% (v/w, of sodium caseinate), with 4 replications. The result indicates that the concentration of 150% (v/w) of sodium caseinate of infused liang-tea produced the best rich antioxidant edible films. The edible film had a thickness 0.20 mm, solubility 13.66%, L* colour value 88.39, a* colour value of -0.23, b* colour value of 5.01, water holding capacity 3.47 (g/g), moisture content 14.11%, and antioxidant activity 41.42%.